A Semiotics Analysis Of Google Search Engine Logos - Nagr i, Rusihan Pusparum (2012)
Our daily life aspects are full of signs including icon, index, and symbol. The objectives of this research are to describe the way Google search engine logos lead to the identity of the event they represent and the meanings of Google search engine logos . The data are the Google logos which are taken from the Google doodle official website . In collecting the data, the writer applied the documentation and observation. The theories used are the Pierce theory and Saussure theory. Pierce emphasized his theory on the representamen, interpretant and object. Then, Saussure emphasized his theory in analyzing sign using the signifier and signified criteria. The type of the research is qualitative interpretative type. The several steps are done to analyze the data. In analyzing the way Google search engine logos lead to the identity of the event they represent , the steps are: analyzing the representamen , analyzing the interpretant , and analyzing the object. In analyzing meaning, the steps are: analyzing signifier and analyzing the signified. This research shows that (1) the events that Google logos represent are : cultural, historical, personal, technological and literature symbol, and (2) the meanings are: referring to cultural, religion, science and entertainment that exist in society.